2017
DOI: 10.1165/rcmb.2016-0239oc
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Sensing and Persistence Genes Are Expressed during the Intragranulomatous Survival of Mycobacterium tuberculosis

Abstract: Although it is accepted that the environment within the granuloma profoundly affects Mycobacterium tuberculosis (Mtb) and infection outcome, our ability to understand Mtb gene expression in these niches has been limited. We determined intragranulomatous gene expression in human-like lung lesions derived from nonhuman primates with both active tuberculosis (ATB) and latent TB infection (LTBI). We employed a non-laser-based approach to microdissect individual lung lesions and interrogate the global transcriptome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 50 publications
(72 reference statements)
1
58
0
Order By: Relevance
“…Adaptations to hypoxia have been implicated to play a prominent role in the dormancy of Mtb 4 . Accumulating evidence has demonstrated that oxygen tension correlates tightly with Mtb growth, the formation of hard, fibrous, hypoxic granulomas, and, eventually, the development of infection 5 . Wayne et al 6 , 7 have pioneered the development of culture conditions that gradually deprive bacteria of oxygen to generate nonreplicating persistent bacilli in vitro as a model for latency.…”
Section: Introductionmentioning
confidence: 99%
“…Adaptations to hypoxia have been implicated to play a prominent role in the dormancy of Mtb 4 . Accumulating evidence has demonstrated that oxygen tension correlates tightly with Mtb growth, the formation of hard, fibrous, hypoxic granulomas, and, eventually, the development of infection 5 . Wayne et al 6 , 7 have pioneered the development of culture conditions that gradually deprive bacteria of oxygen to generate nonreplicating persistent bacilli in vitro as a model for latency.…”
Section: Introductionmentioning
confidence: 99%
“…These paradigms are generally well-supported by observations in NHP models of TB latency and latent TB reactivation due to immune suppression such as following TNF blockade therapy or SIV infection (Diedrich et al, 2010;Mehra et al, 2011;Foreman et al, 2016). In NHPs that have developed LTBI, necropsy reveals well-organized lesions persisting in the lung despite the absence of detectable bacilli (Hudock et al, 2017). In an elegant study of latent TB reactivation in the NHP due to TNF-α blockade, fluorescence labeling of metabolic hotspots along with PET CT imaging of granulomas demonstrated activity in previously affected areas of the lung (Lin et al, 2016).…”
Section: Discussionmentioning
confidence: 78%
“…The relationship between hypoxia and the expression of the dormancy regulon was further validated in the second study from this group, which found that the dormancy regulon was induced in Mtb in association with lesion hypoxia and latency in infected NHPs (Hudock et al. 2017 ). It is interesting to note that the most hypoxic lesions also contained central necrosis and the subsequent accumulation of a lipid-rich caseum within the granuloma.…”
Section: The Dos System and The Dormancy Regulonmentioning
confidence: 87%
“…( 2015 ) and Hudock et al. ( 2017 ) established the Dos system as an essential part of Mtb virulence in vivo and that the expression of genes within the Dos dormancy regulon is associated with local hypoxia. A link between induction of the dormancy regulon and dormant Mtb , however, has yet to be conclusively established in vivo .…”
Section: Conclusion and Directionsmentioning
confidence: 99%